2021
DOI: 10.21037/jtd-20-2779
|View full text |Cite
|
Sign up to set email alerts
|

Surgical septal myectomy outcome for obstructive hypertrophic cardiomyopathy after alcohol septal ablation

Abstract: Background: Although surgical treatment of residual obstruction after alcohol septal ablation (ASA) is often challenging in patients with obstructive hypertrophic cardiomyopathy (OHCM) there are very few relevant clinical reports. Thus, outcomes of surgical septal myectomy (SSM) in this subgroup of patients remain to be determined. Therefore, this study aimed to determine the surgical and follow-up outcomes in patients with OHCM exhibiting residual obstruction after ASA. Methods: We collected case data for 62 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…However, the blood supply of the septum is so abundant and highly variable and includes all other septal branches as well as the posterior descending artery, 4 leading to an unsatisfactory infarcted area that is inadequate to cover the target septal zone. 5 In this case, alcohol failed to be injected into the other septal branches, and there was rich collateral circulation. After ASA, the thick septal branches on CCTA, abundant perfusion on MCE, and unsatisfactory delayed enhancement region on CMR all implied that ASA was not adequate to eliminate blood supply to the basal septum.…”
Section: Discussionmentioning
confidence: 83%
“…However, the blood supply of the septum is so abundant and highly variable and includes all other septal branches as well as the posterior descending artery, 4 leading to an unsatisfactory infarcted area that is inadequate to cover the target septal zone. 5 In this case, alcohol failed to be injected into the other septal branches, and there was rich collateral circulation. After ASA, the thick septal branches on CCTA, abundant perfusion on MCE, and unsatisfactory delayed enhancement region on CMR all implied that ASA was not adequate to eliminate blood supply to the basal septum.…”
Section: Discussionmentioning
confidence: 83%
“…115 The vast majority of patients incur left bundle branch as a result of the operative resection which does not influence later clinical course. 112 Surgeons performing myectomy after an unsuccessful ASA report less consistent operative results and a higher rate of complete heart block, [116][117][118] underscoring that myectomy is the preferred initial procedure to avoid myocardial scarring, heart block and other potential adverse consequences of ASA.…”
Section: Clinical Results Of Surgical Myectomymentioning
confidence: 99%
“…CMR can be used during the follow-up to quantify the size and location of the iatrogenic infarct. The use of CMR is also helpful in the case of procedural failure to evaluate the reasons for unsuccess (i.e., the iatrogenic infarct is too small or outside the target area) [60]. In the Numerous studies have shown that approximately 90% of patients undergoing a successful procedure experience an improvement of functional status (i.e., post-procedural NYHA class I-II), and in 80% of cases, there is a significant reduction in LVOTO [53].…”
Section: How To Assess Procedural Success?mentioning
confidence: 99%
“…CMR can be used during the follow-up to quantify the size and location of the iatrogenic infarct. The use of CMR is also helpful in the case of procedural failure to evaluate the reasons for unsuccess (i.e., the iatrogenic infarct is too small or outside the target area) [60]. In the event of failure, surgical myectomy may be performed as a rescue strategy.…”
Section: How To Assess Procedural Success?mentioning
confidence: 99%
See 1 more Smart Citation